PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBASIS EDMODO TERHADAP HASIL BELAJAR PESERTA DIDIK PADA TOPIK GELOMBANG BUNYI - A Halim; Rini Safitri; Yusrizal Yusrizal; Miswatul Hasanah (Postgraduate, University of Mataram, 2021)
This study aims to see the effect of the Edmodo-based Flipped Classroom learning model on student learning outcomes. The method used in this study is a quasi-experimental design with The Nonequivalent Control Group Design. The instruments used are in the form of choice questions to measure learning outcomes and student response questionnaires to the use of the Edmodo-based flipped classroom model. Learning outcomes were analyzed using an independent sample t-test based on the acquisition of N-gain. The results showed that there was a significant difference in improving learning outcomes between the control class and experimental class with tcount = 3.06 > ttable = 2.02 with a two-tailed significance value (Sig. 2-tailed) smaller than Â = 0.05 which is 0.004. There is a significant difference in learning outcomes, indicating that there is an effect caused by the implementation of Edmodo-based flipped classrooms. The results of data analysis showed that the increase in student learning outcomes in the experimental class by applying the Edmodo-based flipped classroom model was better than the control class without the Edmodo-based flipped classroom model. Around88.4% of students gave a positive attitude towards the use of Edmodo-based flipped classrooms.